INTEGRASI PROGRAM SOCIAL EMOTIONAL LEARNING KE DALAM PROGRAM LATIHAN TARUNG DERAJAT UNTUK PENGEMBANGAN SOCIAL EMOTIONAL DALAM RANGKA POSITIF YOUTH DEVELOPMENT - Anne Patmah Annisa, - (2021)
This research aims to determine the influence and differences of social emotional development in the integrated social emotional learning of tarung derajat training group, the non-integrated social emotional learning group and the group that does not participate in sports training to develop the positive youth. The method used in this study is a pre-test-post-test control group design with more than one experimental group. The instrument used is Social and Emotional or Non-cognitive Nationwide Assessment (SENNA). The results showed that there was a difference in the effect between the degree fighting training group that was integrated with social emotional learning and the non-integrated social emotional learning group of combat training on social emotional development. Meanwhile, the integrated group is superior to the non-integrated group. There is a difference in the effect between the integrated social emotional learning group and the group that does not take part in sports training on social emotional development, the integrated group is superior to the group that does not take part in sports training and there is a different effect between the group that is not integrated into social emotional learning and the group that does not take part in the exercise. exercise on social emotional development, the group that exercises better than those who do not exercise.